Marketing Strategy to Increase Room Occupancy Rates at Yama Resort - Mononimbar, Virginia; Wewengkang, Silvana A.R.; Pangemanan, Jemmy R.; Lumataw, Arthur (Journal of Multi-Disciplines Science, 2024)
This research aims to identify marketing strategies to increase room occupancy rates at Yama Resort. The research method used is the Qualitative Method. Data was obtained through observation, interviews and literature study. This research shows that five marketing strategies can be implemented to increase room occupancy rates. Furthermore, eight strategies can be implemented based on the strength, weakness, opportunity and treatment (SWOT) analysis. Yama Resort management needs to focus on existing strengths and collaborate with business people to attract more guests. It will ultimately impact increasing the room occupancy rate at Yama Resort.